INTERNAL CONTROL SYSTEM IMPLEMENTATION AND FINANCIAL ACCOUNTABILITY: A STUDY ON BLUD PUSKESMAS IN WONOGIRI REGENCY - Sutaryo, Sutaryo; Muhtar, Muhtar; Winarna, Jaka (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study is an empirical research that aims to examine the role of Internal Control System (SPI) in overseeing the financial management accountability of BLUD Puskesmas in Wonogiri Regency. This research uses secondary data from the audit results of BLUD financial statement in 2022 and 2023. This research finds that the implementation of SPI at BLUD Puskesmas in Wonogiri Regency is quite adequate, although there are still several Puskesmas that are classified as inadequate. Empirical analysis shows that control activities, information and communication, and monitoring demonstrate a positive effect on the BLUD financial accountability. However, the role of the control environment and risk assessment is not yet optimum in maintaining accountability. This research provides several practical recommendations based on the empirical findings. BLUD Puskesmas in Wonogiri Regency needs to improve the quality of SPI implementation, especially in strengthening the control environment and improving risk assessment. BLUD Puskesmas in Wonogiri can recruit more human resources to reduce the burden of concurrent tasks, as well as ensure consistent implementation of financial management tasks and authority in accordance with the existing organizational structure. BLUD financial management personnels are also suggested to improve their competency through adequate training. Apart from that, information and communication as well as monitoring must be continuously improved by coordinating with BLUD’s upper offices in Wonogiri Regency, supported by the application of information technology. Finally, it can be expected that the quality of SPI can improve and become stronger in maintaining accountability in BLUD financial management.